The Preliminary Study of Electrigens Potential from Wastewater as The Manifestation Of "Khalifah Fil Tadbir" Conception - Hafsan, Hafsan; Asaad, Andi Indra Jaya; Arsyad, Muh Ali; Ahmad, Arifuddin (Jurnal Biotek, 2024)
This study reveals that the super-intensive shrimp farming waste from Punaga can be used as a source of electricity through a bio-electrogenic process based on indigenous potential bacteria from the waste. The results show that four types of potential bacteria isolated from the super-intensive shrimp farming waste can each produce a significant average power density. Bacteria isolate D (Bacillus sp) showed the highest electrogenic potential with an average power density of 38.55±0.87 mW/m², followed by bacteria isolate B (Pseudomonas sp) with an average power density of 34.72±2.80 mW/m², bacteria isolate C (Bacillus sp) with an average power density of 29.90±5.26 mW/m², and bacteria isolate A (Bacillus sp) with an average power density of 25.90±1.69 mW/m². This study shows that the super-intensive shrimp farming waste from Punaga can be utilized as a source of electricity through a bio-electrogenic process using certain potential bacteria, such as Bacillus sp and Pseudomonas sp isolates. The development of waste treatment technology as a source of electricity through the bio-electrogenic process can provide a significant contribution to addressing global energy and environmental issues. This can be considered an implementation of the concept of "khalifah fil tadbir", in which humans act as stewards of the earth, responsible for using natural resources wisely and being accountable for the resulting environmental impacts.